Circulating Extracellular Vesicles Are Strongly Associated With Cardiovascular Risk Markers - Zhou, Ruihan; Bozbas, Esra; Allen-Redpath, Keith; Yaqoob, Parveen (Frontiers in Cardiovascular Medicine, 2022)
Background Extracellular vesicles (EVs) are submicron membrane-bound vesicles released from various cells, which are emerging as a potential novel biomarker in cardiovascular diseases (CVDs) due to their procoagulatory and prothrombotic properties. However, there is little information about the relationships between circulating EVs and conventional and thrombogenic risk markers of CVDs. Objective To investigate the relationships between circulating EVs, conventional cardiovascular risk markers and thrombogenic markers in subjects with moderate risk of CVDs. Design Subjects (n = 40) aged 40-70 years with moderate risk of CVDs were recruited and assessed for body mass index, blood pressure and plasma lipid profile, as well as platelet aggregation, clot formation, thrombin generation and fibrinolysis. Numbers of circulating EVs were assessed by Nanoparticle Tracking Analysis and flow cytometry. A range of assays were used to assess the procoagulatory activity of plasma and circulating EVs. Results Circulating EV numbers were positively associated with body mass index, blood pressure, plasma triacylglycerol concentration and overall CVD risk. Higher circulating EV numbers were also associated with increased thrombin generation and enhanced clot formation, and EVs isolated from subjects with moderate CVD risk promoted thrombin generation ex vivo. Higher numbers of endothelial-derived EVs were associated with a greater tendency for clot lysis. Plasma triacylglycerol concentration and diastolic blood pressure independently predicted circulating EV numbers, and EV numbers independently predicted aspects of thrombin generation and clot formation and 10-year CVD risk. Conclusion Circulating EVs were strongly associated with both conventional and thrombogenic risk markers of CVDs, and also with overall CVD risk, highlighting a potentially important role for EVs in CVDs.